Effect of feeding Aspergillus awamori and canola seed on the growth performance and muscle fatty acid profile in broiler chicken. (5th December 2014) - Saleh, Ahmed A; Hayashi, Kunioki; Ijiri, Daichi; Ohtsuka, Akira
Abstract The aim of this study was to examine effects of dietary supplementation with Aspergillus awamori and feeding canola seed on the growth and fatty acid profile in broilers. Twenty‐eight chicks (15 days old) were assigned to the following groups: (1) control, fed a basal diet; (2) awamori, fed the basal diet supplemented with 0.05% A. awamori; (3) canola, fed a diet containing 5% canola seed; and (4) canola + awamori, fed the canola diet supplemented with A. awamori (seven birds/group). Body weight gain was increased by A. awamori but not influenced by canola seed. Breast muscle weight was increased in either awamori or canola groups. Although plasma triglyceride and cholesterol were decreased by feeding A. awamori or canola seed, fat content in the breast muscle were increased, accompanied by decrease in saturated fatty acids and increase in unsaturated fatty acids. Moreover, decreased thiobarbituric acid reactive substance and increased α‐tocopherol content in the breast muscle was observed in all experimental groups. In conclusion, these results suggested that feeding canola seed and A. awamori might improve growth performance, and modified muscle fatty acid profile and α‐tocopherol content, suggesting that they may improve meat quality.